Comparative evaluation of the quality of Papanicolaou staining at different intervals of fixation times using 96% ethyl alcohol - Shirley Borges S. Quintana; Fabiano L. Carvalho; Glória Regina F. Silva; Maria Beatriz T. Campos; Maria Conceição S. Maia; Mario Lucio C. Araújo Júnior; Marcel S. B. Quintana
ABSTRACT Introduction: Fixation of cytological smears consists of immediate immersion in appropriate fixative, in order to preserve cellular morphological characteristics, it is essential for the microscopic examination and diagnostic interpretation. Objective: To evaluate the influence of fixation times on the morphological and staining characteristics of samples fixed in ethanol and stained by the Papanicolaou method. Method: Experimental, quantitative and qualitative research was carried out on 99 samples of the jugal mucosa scrapings from 33 participants, fixed in 96% ethyl alcohol in three different times. Group A: 15 minutes; group B: 30 minutes; group C: seven days. The quality of staining was categorized in Optimal, Good, Regular and Poor, with subsequent recategorization at optimal and non-optimal. To verify the association among the groups and the categories, Fisher's exact test was performed, with significance level of 0.05. Results: From the 99 stained slides, 19 were discarded due to acellularity, remaining 80 slides. From these, 28 in group A, 26 in group B and 26 in group C were evaluated. In Group A, optimal quality was found in 60.7% (n = 17), good in 28.6% (n = 8), regular in 10.7% (n = 3) and poor in 0% (n = 0). In group B optimal was found in 61.5% (n = 16), good in 30.8% (n = 8), regular in 7.7% (n = 2) and poor in 0% (n = 0). In group C, optimal was found in 92.3% (n = 24), good in 7.7% (n = 2), regular in 0% (n = 0) and poor in 0% (n = 0). In the three groups, there was no representation of the Poor category. Conclusion: The results suggest that there is a significant difference in the staining quality (p-value = 0.01) according to the fixation time.